The Effect of Audit Opinion, Financial Distress, Company Growth on Audit Switching in Manufacturing Companies Listed on the Indonesia Stock Exchange - Muhammad Ridha Habibi Z; Faisal; Nova Mahendra (Outline Publisher, 2023)
This study aims to determine the effect of Audit Opinion, Financial Distress, Company Growth on Audit Switching partially and simultaneously in manufacturing companies listed on the Indonesia Stock Exchange (IDX). The population in this study are manufacturing companies listed on the Indonesia Stock Exchange, as many as 177 companies. From the population, selected by purposive sampling technique and obtained as many as 47. The results partially show that opinion has no effect and is not significant, Financial Distress has no and no significant effect on Auditor Switching, while Company Growth has a significant effect on Auditor Switching. The results of the study simultaneously show that Audit Opinion, Financial Distress, Company Growth have a significant effect on Auditor Switching. The coefficient of determination (Nagelkerke's R Square) explains that Auditor Switching can be explained by Audit Opinion, Financial Distress, Company Growth. While the remainder of the Auditor Switching variable can be explained by other variables not examined in this study, such as management turnover, the size of the Public Accounting Firm.